2021
DOI: 10.24018/ejfood.2021.3.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Climate Variability on Zea Mays Productivity over Glen Research Station: South Africa

Abstract: Rainfall and temperature are one of the key environmental parameters that determines the development of a crop and livestock from one growing stage to maturity. Furthermore, temperature is critical beyond maturity but to post harvesting and storage. Rainfall is fundamental in the selection of planting dates, cultivar selection and planting density. Whereas, temperature is essential for calculation of chill and heat units for determining conducive environmental conditions for crop productivity and livestock wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Understanding the different climatic factors influencing fungal survival, development, metabolic activity, and interaction with other organisms such as host plants, is vital for deterring their overall behaviour, leading to toxin contamination [26]. In a study by Zuma-Netshiukhwi et al [32], it was determined that a temperature rise by 1 • C or 2 • C will result in a roughly 20% to 25% decrease in grain yield as a result of CC. Kachapulula et al [12] reported high levels of AFs in maize and groundnuts in a drier and low rainfall zone as compared to cooler and high-rainfall zones.…”
Section: Climate Change and Aflatoxin Contamination Of Maizementioning
confidence: 99%
“…Understanding the different climatic factors influencing fungal survival, development, metabolic activity, and interaction with other organisms such as host plants, is vital for deterring their overall behaviour, leading to toxin contamination [26]. In a study by Zuma-Netshiukhwi et al [32], it was determined that a temperature rise by 1 • C or 2 • C will result in a roughly 20% to 25% decrease in grain yield as a result of CC. Kachapulula et al [12] reported high levels of AFs in maize and groundnuts in a drier and low rainfall zone as compared to cooler and high-rainfall zones.…”
Section: Climate Change and Aflatoxin Contamination Of Maizementioning
confidence: 99%
“…Weather prediction is important due to its broad impact on agriculture, transportation, and disaster management sectors [1]. Accurate forecasts contribute to economic improvements by facilitating planning and decision-making [2].…”
Section: Introductionmentioning
confidence: 99%